Evaluation of 16S rRNA Gene Sequence for DNA Barcoding of Tuna Fish - Kolondam, Beivy J (Sam Ratulangi University, 2022)
For fish product authentication, DNA barcoding has been a reliable tool. This is due to its requirement of a small amount of tissue sample in order to conduct a full analysis for species identification. This research aimed to conduct an assessment for the use of 16S rRNA gene sequence for tuna fish identification through DNA barcoding. Previous in silico studies using the COI gene and CYB gene were conducted using the same tuna fish specimens. A comparison of 16S rRNA gene sequence between Bluefin tuna (five species), Yellowfin tuna (three species), and another group of tuna (five species) showed the reliability of this gene in differentiating all species represented by the respective specimens. The multiple sequence alignment of 1695 bp in this research is reliable for accurate identification. All specimens of Thunnus (Bluefin group and Yellowfin group) were able to be differentiated with other genera (Auxis, Euthynnus, and Katsuwonus) group in 27 sites. The other tuna fish genera group members are similar in 27 sites and the member Thunnus group has a polymorphism in the same location. The similarity among the Bluefin group is 99.3% to 99.8%. The similarity among Yellowfin group is 99.6% to 99.9%. The similarity among the other group is 97.5% to 99.5%. In conclusion, the 16S rRNA gene is a reliable marker for DNA barcoding of tuna fish.Keywords: DNA barcoding; 16S rRNA gene; tuna fishAbstrakUntuk kepentingan autentikasi produk-produk dari ikan, DNA barcoding merupakan perangkat yang dapat diandalkan. Ini disebabkan karena metode ini hanya membutuhkan sedikit sampel jaringan untuk analisis identifikasi spesies. Penelitian ini bertujuan untuk melakukan asesmen penggunaan sekuens gen 16S rRNA untuk identifikasi ikan tuna melalui DNA barcoding. Studi in silico sebelumnya untuk gen COI dan gen CYB dilaksanakan menggunakan spesimen ikan tuna yang sama. Perbandingan sekuens gen 16S rRNA antara kelompok ikan tuna Bluefin (lima spesies), kelompok ikan tuna Yellowfin (tiga spesies), dan kelompok ikan tuna jenis lain (lima spesies) menunjukkan kemampuan gen ini dalam membedakan semua spesies. Dari hasil yang diperoleh, penjajaran multisekuens dari 1695 bp dapat diandalkan untuk indentifikasi yang akurat. Semua spesimen genus Thunnus (kelompok Bluefin dan kelompok Yellowfin) dapat dibedakan dengan spesimen lainnya pada 27 titik nukleotida. Kelompok tuna jenis lain juga memiliki nukleotida yang seragam di 27 lokasi dibandingkan dengan yang dari genus Thunnus. Tingkat kesamaan antar spesimen kelompok tuna Bluefin yaitu 99,3% sampai 99,8%. Tingkat kesamaan antar spesimen kelompok tuna Yellowfin yaitu 99,6% sampai 99,9%. Tingkat kesamaan antar kelompok tuna jenis lain yaitu 97,5% sampai 99,5%. Dari penelitian ini dapat disimpulkan bahwa gen 16S rRNA merupakan gen yang dapat diandalkan untuk DNA barcoding ikan tuna.Kata-kata kunci: DNA barcoding; gen 16S rRNA; ikan tuna